Depression and smoking: A 5-year prospective study of patients with major depressive disorder - Holma, Irina; Holma, Mikael; Melartin, Tarja; Isometsä, Erkki; Ketokivi, Mikko (Depression and Anxiety, 2013)
Background Major depressive disorder (MDD) and smoking are major public health problems and epidemiologically strongly associated. However,the relationship between smoking and depression and whether this is influenced by common confounding factors remain unclear,in part due to limited longitudinal data on covariation. Methods In the Vantaa Depression Study,psychiatric out- and inpatients with DSM-IV MDD and aged 20-59 years at were followed from baseline to 6 months,18 months,and 5 years. We investigated course of depression,smoking,and comorbid alcohol-use disorders among the 214 patients (79.6% of 269) participating at least three time points; differences between smoking versus nonsmoking patients,and covariation of MDD,smoking,and alcohol-use disorders. Results Overall,31.3% of the patients smoked regularly,41.1% intermittently,and 27.6% never. Smokers were younger,had more alcohol-use disorders and Cluster B and C personality disorder symptoms,a higher frequency of lifetime suicide attempts,higher neuroticism,smaller social networks,and lower perceived social support than never smokers. Smoking and depression had limited longitudinal covariation. Depression,smoking,and alcohol-use disorders all exhibited strong autoregressive tendencies. Conclusions Among adult psychiatric MDD patients,smoking is strongly associated with substance-use and personality disorders,which may confound research on the impact of smoking. Rather than depression or smoking covarying or predicting each other,depression,smoking,and alcohol-use disorders each have strong autoregressive tendencies. These findings are more consistent with common factors causing their association than either of the conditions strongly predisposing to the other. © 2013 Wiley Periodicals,Inc.
Keywords: Alcohol; Adult; Alcohol abuse; Alcohol consumption; Article; Comorbidity; Controlled study; DSM-IV; Female; Follow up; Human; Major clinical study; Major depression; Male; Mental patient; Neurosis; Personality disorder; Priority journal; Prospective study; Smoking; Smoking habit; Social network; Social support; Suicide attempt; Alcoholism; Comorbidity; Depressive Disorder; Major; Female; Finland; Health Surveys; Humans; Middle Aged; Personality Disorders; Prospective Studies; Smoking; Social Support; Suicide; Attempted; Alcoholism; Major depressive disorder; Personality disorders; Tobacco smoking; ODS 3 - Salud y bienestar